EFFECT OF SOME PARAMETERS ON THE PRODUCTION OF RIFAMYCINS BAND SV BY AMYCOLATOPSIS MEDITERRANEI - SHAHED , KAMAL Y.I EL-; FARID, MOHAMED A. (Biological Sciences - PJSIR, 2022)
The effect of different parameters on the production of rifamycins Band SV were studied. The optimum production was obtained after four days. The concentration ratio of starch to glucose at 20: 10 g/L was favourable for the antibiotic production. The effect of nitrogen compounds indicated that the phenylenediamine, potassium phthalimide and uracil have a stimulating effect on the production of rifamycin B by Amycolatopsis mediterranei similar to the barbital; specially uracil at 2 g/L.